2007
DOI: 10.1021/jf0710480
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprofiling of Bifidobacterial Consumption of Human Milk Oligosaccharides Demonstrates Strain Specific, Preferential Consumption of Small Chain Glycans Secreted in Early Human Lactation

Abstract: The molecular basis by which human breast milk supports the development of a protective intestinal microbiome in infants is unknown. After lactose and lipids, human milk oligosaccharides (HMOs) are quantitatively the third largest and most diverse component of breast milk. In this work, glycomic profiling of HMO consumption by bifidobacteria using Fourier transform ion cyclotron resonance mass spectrometry reveals that one species, Bifidobacterium longum biovar infantis ATCC 15697, an isolate from the infant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
364
5
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(396 citation statements)
references
References 22 publications
19
364
5
4
Order By: Relevance
“…1 Glycoprofiling results by LoCascio et al 22 provide molecular and mechanistic evidence that specific strains of bifidobacteria have an affinity for selected classes of HMO. 8,11 This suggests that the diversity of specific oligosaccharide structures found within human milk do not provide a direct source of nutrition to the infant, but rather act as specific substrates to assist the growth of selected beneficial bacteria, that in their own right support the development and protection of the neonate.…”
Section: The Bifidogenic (Prebiotic) Effect Of Human Milk Oligosacchamentioning
confidence: 99%
See 3 more Smart Citations
“…1 Glycoprofiling results by LoCascio et al 22 provide molecular and mechanistic evidence that specific strains of bifidobacteria have an affinity for selected classes of HMO. 8,11 This suggests that the diversity of specific oligosaccharide structures found within human milk do not provide a direct source of nutrition to the infant, but rather act as specific substrates to assist the growth of selected beneficial bacteria, that in their own right support the development and protection of the neonate.…”
Section: The Bifidogenic (Prebiotic) Effect Of Human Milk Oligosacchamentioning
confidence: 99%
“…21 An extraordinary characteristic of the intestinal environment of breastfed infants is the selective nourishment and protective support provided by the intestinal microbiotia. 22 The term "prebiotic" was introduced and defined by Gibson and Roberfroid as "a non-digestible food ingredient that beneficially affects the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon". 23,24 Although…”
Section: The Bifidogenic (Prebiotic) Effect Of Human Milk Oligosacchamentioning
confidence: 99%
See 2 more Smart Citations
“…The latter strategy allows also bystander bacteria to exploit the liberated sugars (Rakoff‐Nahoum et al ., 2016) with possibilities of cross‐feeding of enteric pathogens (Ng et al ., 2013). Some bifidobacteria showed preferences for fucosylated or small mass HMO typically produced through the first month of lactation (LoCascio et al ., 2007). The pioneers in that emerging field even suggested that mothers use a ‘glycan code’ when synthesizing HMO during the breastfeeding period that ‘instruct’ the gut in their infants what particular bacteria should get a nutritional push during a given time interval.…”
Section: Biome Engineering: Modifying the Nutrient Inputmentioning
confidence: 99%